The Quadrangulation appraisal technique as research strategy for the Negros Oriental Ancestral Domain Research Project - Elman, Nichol R.; Pioquinto, Ceres E. (Silliman Journal, 2023)
This research approach was adapted from the model used by Dr. Nichol R. Elman in his dissertation, “Rural People Response to an Integrated Development Project of a Philippine Institution of Higher Learning,” University of the Philippines Los Bafios College, Laguna, 1993. The research project was commissioned and funded by the Provincial Environment and Natural Resources office of Negros Oriental in pursuance of the Constitutional mandate “for the recognition and protection of the rights of the indigenous cultural communities to their ancestral lands and domains to ensure their economic, social and cultural well-being” (Philippine Constitution 1987, Section 22, Article II; Section 5, Article XII; and Section 6, Article XII). Indigenous Cultural Communities (ICCs), also called Indigenous Peoples (IPs) refer to “a homogenous society identified by seif-ascription and ascription by others, who have continuously lived as community on communally bounded and defined tenitory, sharing common bonds of language, customs, traditions and other distinctive cultural traits, and who, through resistance to the political, social and cultural inroads of colonization, became historically differentiated from the majority of Filipinos” (Department Administrative Order No. 02, Series of 1993, Section 3, Article 1). The Provincial Special Task Force for Ancestral Domains (PSTFAD) refers to the Special Task Force based in specific Provincial Environment and Natural Resources Offices (PENRO) which is responsible for the identification, delineation, recognition and management of ancestral domain claims as defined in the Department Administrative Order No. 02, Series of 1993.